Market Demand and Economic Performance Analysis of PT. Indonesia Hijau’s Cocoa Industry Competitiveness - Sainab; Kautsar, Muthia Natasya (Tarjih : Agribusiness Development Journal, 2025)
Cocoa plays a significant role in promoting regional and agroindustrial development, particularly as a raw material for the food and beverage industry. Sulawesi, as Indonesia’s largest cocoa-producing region, offers good-quality cocoa beans; however, its processed products have yet to gain a strong foothold in international markets. PT. Indonesia Hijau, a cocoa processing company, faces several challenges in sustaining its business, including market demand fluctuations, production cost efficiency, raw material price volatility, shifting consumer preferences, and competition from imported products.This study aims to evaluate market demand trends, economic performance, and the competitive advantages of PT. Indonesia Hijau. Two main analytical approaches were employed: market demand trend analysis and Policy Analysis Matrix (PAM). The findings show that demand for PT. Indonesia Hijau’s cocoa products fluctuated from 2018 to 2023, with a decline during the COVID-19 pandemic (2020–2021) and a recovery afterward. Chocolate bar and cocoa powder products demonstrated consistent growth post-pandemic, indicating promising market potential for processed cocoa. PAM analysis results reveal that PT. Indonesia Hijau holds both competitive and comparative advantages, as reflected by a A PCR of 0.76 and a DCR of 0.79 both falling below the threshold of one indicate that the company's production operations are cost effective and demonstrate strong potential for continued economic development. These findings provide practical insights for cocoa processors and policymakers to enhance supply chain efficiency and strengthen the global competitiveness of Indonesian cocoa products.